No sea demandado al rey por qué hace así. Power and powers in the Chronicles of García de Eugui and García López de Roncesvalles (History Journal «Jerónimo Zurita», 2024)
In the context of the reign of Charles III of Navarre, two chroniclers linked to the king's circle, Bishop García de Eugui and the treasurer García López de Roncesvalles, construct their narratives for the greater glory of the monarchy. This study attempts to establish the similarities and differences they present, both in their approaches to the construction of royal power throughout history and in the roles they attribute to the different privileged groups in such development.
Keywords: Chronicles; Navarre; Royal Power; Nobility; Church; Bourgoisie